A Field Study of the Effect of Noise and Whole-Body Vibration Exposure on Heavy Equipment Drivers’ Auditory System Function - Seyyed Mohammad Javad Golhosseini; Mohsen Aliabadi; Rostam Golmohammadi; Maryam Farhadian; Mehdi Akbari (بهداشت و ایمنی کار)
Introduction: Despite the numerous studies on occupational noise-induced hearing loss, there is limited documentation on the vibration effects on the workers’ auditory system. Heavy equipment drivers are exposed to high levels of whole-body vibration (WBV) and noise. Therefore, this study aims to investigate the heavy equipment drivers’ auditory response to WBV exposure and combined exposure to noise and WBV. Material and Methods: 30 male heavy equipment drivers with an average age of 32.40 ± 4.91 years participated in this study, which was designed based on the repeated measurements model. During 3 defined scenarios of exposure to WBV, combined exposure to noise and WBV, as well as the scenario without exposure, the drivers’ auditory response was measured using distortion product otoacoustic emissions (DPOAE). Statistical analyses were performed by IBM SPSS-25 software. Results: The range of heavy equipment in-cabin noise was 84-89 dB. Also, the most exposure of drivers to WBV was obtained in the Z axis with an average acceleration of 1.29 m/s2. The DPOAE amplitude of the drivers in all three investigated scenarios showed significant changes (P<0.05); But in comparison between different scenarios, exposure to WBV and combined exposure to noise and WBV had a significant effect on the response of the auditory system of the participants in the study compared to the scenario without exposure (P<0.05). Also, there was a significant difference in the changes of the DPOAE amplitude in different frequencies; Thus, the most changes in the DPOAE amplitude were observed in the frequencies of around 4000 Hz. Conclusion: The results of this study showed the damaging consequences of exposure to noise and WBV on the auditory response; In addition, the present study provided evidence of synergistic effects of combined exposure to noise and WBV on heavy equipment drivers.